MULTIPLYING SUCCESS: THE INFLUENCE OF BEHAVIOR, INTRINSIC MOTIVATION, AND INNOVATION OF FEMALE HANDICRAFT ENTREPRENEURS - Purwani, Setyaningrum Retno; Wahyu, Wirjawan Tri; Nining, Yuningsih (Jurnal Aplikasi Manajemen, 2018)
This research aims to analyze the influence of behavior, intrinsic motivation and innovation to multiply the success of the organization. The subjects in this research are female handicraft entrepreneurs in Bekasi. The approach used is a quantitative method with the variables are Examining the influence of behavior, intrinsic motivation and innovation to the success of female handicraft entrepreneur in Bekasi andThe influence of Innovation mediated by organizational culture on the success of femalehandicraft entrepreneurs. The sample of this research was 100 of 150 respondents from the population of female recycled handicraft entrepreneurs.The data collected from secondary and primary data. The primary data were obtained by Interview, Forum Group Discussion, Questioner, and observation.The sampling technique using judgment sampling method and data analysis is processed by using Structural Equation Modeling (SEM) which is assisted by the application of Moment Structure Analysis (AMOS) version 22.0. The Results are the behavior of female handicraft entrepreneurs affects organizational culture, as well as intrinsic motivation, affect the organizational culture, and the ability to innovate mediated by the organizational culture affects the success of woman handicraftentrepreneurs, which means the ability to innovate as a dominant mediation variable.